Interfacing solid‐state nanopores with gel media to slow DNA translocations. Issue 15 (3rd June 2015) - Waugh, Matthew; Carlsen, Autumn; Sean, David; Slater, Gary W.; Briggs, Kyle; Kwok, Harold; Tabard‐Cossa, Vincent
Abstract : We demonstrate the ability to slow DNA translocations through solid‐state nanopores by interfacing the trans side of the membrane with gel media. In this work, we focus on two reptation regimes: when the DNA molecule is flexible on the length scale of a gel pore, and when the DNA behaves as persistent segments in tight gel pores. The first regime is investigated using agarose gels, which produce a very wide distribution of translocation times for 5 kbp dsDNA fragments, spanning over three orders of magnitude. The second regime is attained with polyacrylamide gels, which can maintain a tight spread and produce a shift in the distribution of the translocation times by an order of magnitude for 100 bp dsDNA fragments, if intermolecular crowding on the trans side is avoided. While previous approaches have proven successful at slowing DNA passage, they have generally been detrimental to the S/N, capture rate, or experimental simplicity. These results establish that by controlling the regime of DNA movement exiting a nanopore interfaced with a gel medium, it is possible to address the issue of rapid biomolecule translocations through nanopores—presently one of the largest hurdles facing nanopore‐based analysis—without affecting the signal quality or capture efficiency.